Activity of Antistaphylococcal Lysin CF-301 against Contemporary Staphylococcus aureus Clinical Isolates from the USA and Europe. (4th October 2017) - Oh, Jun; Traczewski, Maria; Schuch, Raymond
Abstract: Background: CF-301 is a novel, recombinantly-produced bacteriophage-derived lysin (cell wall hydrolase) and is the first agent of this class in the US to enter into clinical development for the treatment of bacteremia including endocarditis due to S. aureus . Hallmark features of CF-301 include rapid and pathogen-specific bacteriolytic activity, synergy with antibiotics, biofilm-disrupting activity, a low propensity for resistance, and the capacity to suppress antibiotic resistance. This is the first report of an international surveillance study for CF-301. Methods: 349 methicillin-sensitive and –resistant S. aureus (MSSA and MRSA, respectively) isolates were collected from various infection sources at multiple hospitals from 2015–2017 throughout the US, Greece, Hungary and Italy. In addition to the contemporary isolates, a set of 149 MSSA and MRSA clinical isolates from 2011 were also obtained from US hospital sources. MICs for CF-301 were determined using a new antimicrobial susceptibility testing (AST) medium for broth microdilution recently endorsed by Clinical and Laboratory Standards Institute (CLSI) for use with CF-301. The testing medium consists of cation-adjusted Muller Hinton Broth supplemented with 25% horse serum and 0.5 mM DTT (CAMHB-HSD). Susceptibility to conventional antibiotics was also examined in this study using standard methodology (CLSI document M07-A10) and included: vancomycin, trimethoprim-sulfamethoxazole, daptomycin, oxacillin, linezolid, clindamycin, and cefazolin. Results: CF-301 had MIC50, MIC90, and MIC100 values of 0.5, 1, and 2 μg/mL, respectively, against each set of contemporary MSSA ( n = 176) and MRSA ( n = 173) clinical isolates. There were no differences noted with respect to the geographic source (in the US and Europe) of isolates. Furthermore, the CF-301 MICs reported here for 2015–2017 isolates were identical to that observed for MSSA and MRSA isolates from 2011. Conclusion: CF-301 demonstrated potent in vitro activity against a total of 498 clinical S. aureus isolates from a range of human infections (including bacteremia) and different geographies. Contemporary clinical isolates did not demonstrate reduced susceptibility to CF-301 compared with the 2011 isolates. Disclosures: J. Oh, ContraFect Corp: Employee, Salary; R. Schuch, ContraFect Corp: Employee, Salary